2007
DOI: 10.1111/j.1398-9995.2007.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the burden of allergic rhinitis in Europe

Abstract: Allergic rhinitis remains a significant health problem because of the high burden of symptoms and its impact on general well being and HRQoL among patients consulting for this condition. Overall, there was a poor correlation between patients and physicians in the reporting of disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
295
5
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(335 citation statements)
references
References 29 publications
10
295
5
13
Order By: Relevance
“…Like asthma (57), allergic rhinitis is known to affect social, school and professional life as well as sleep (58)(59)(60). However, there is no existing study on NAR.…”
Section: Social Consequencesmentioning
confidence: 99%
“…Like asthma (57), allergic rhinitis is known to affect social, school and professional life as well as sleep (58)(59)(60). However, there is no existing study on NAR.…”
Section: Social Consequencesmentioning
confidence: 99%
“…Despite these clinical study results, conflicting data exist regarding the prescription rates for medications for the treatment of AR. The prescription rates for AH, a combination of AH and INS, and INS alone were 42.8%, 31.4%, and 14.8%, respectively, in a pan-European study13 and 31.5%, 42.3%, and 21.5%, respectively, in an American study12. Interestingly, the prescription rate for a combination of AH and INS was much higher (66%) in a survey in Spain37.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, several clinical trials have shown that no clinical advantages exist for combination therapy of SAR, compared with INS monotherapy7–11. Although INSs could be considered as the most efficient drugs among several classes of medications for the treatment of AR, the proportion of prescriptions for AHs and combination therapy of AH and INS were both higher than that for INS monotherapy according to surveys conducted in the US12 and in Europe13.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinoconjucntivitis is the associated watery eyes, itching, burning/irritability, redness and injection of the conjunctiva which has been documented in 71% of European patients who concurrently had nasal symptoms [6].…”
Section: Allergic Rhinitismentioning
confidence: 99%